Cathelicidin-related antimicrobial peptide promotes neuroinflammation through astrocyte-microglia communication in experimental autoimmune encephalomyelitis - Bhusal, Anup; Nam, Youngpyo; Seo, Donggun; Rahman, Md Habibur; Hwang, Eun Mi; Kim, Seung-Chan; Lee, Won-Ha; Suk, Kyoungho (John Wiley & Sons Inc., 2022)
Cathelicidin-related antimicrobial peptide (CRAMP) is an effector molecule of the innate immune system with direct antimicrobial and immunomodulatory activities; however, its role in neuroinflammatory responses and related diseases is not clearly understood. In particular, the expression of CRAMP and its functional role has not been previously studied in experimental autoimmune encephalomyelitis (EAE) or multiple sclerosis (MS). Here, we investigated the role of CRAMP in neuroinflammation, using an EAE mouse model of MS and postmortem patient tissues. We found that the CRAMP expression was increased in the spinal cords of EAE-induced mice. Immunofluorescence analysis revealed that CRAMP is mainly induced in reactive astrocytes in the inflamed spinal cord of EAE mice. A similar pattern of the LL-37 (human CRAMP) expression was observed in the brain and spinal cord tissues of patients with MS. An intrathecal injection of the CRAMP peptide in EAE mice accelerated the onset of symptoms and increased disease severity with augmented expression of inflammatory mediators, glial activation, infiltration of inflammatory cells, and demyelination. In addition, shRNA-mediated knockdown of Cramp in the spinal cord resulted in a milder disease course with less inflammation in EAE mice. We identified FPR2 on microglia as a CRAMP receptor and demonstrated that CRAMP potentiates IFN-gamma-induced microglial activation via the STAT3 pathway. Taken together, our findings suggest that CRAMP is a novel mediator of astrocyte-microglia interactions in neuroinflammatory conditions such as EAE. Thus, CRAMP could be exploited as a biomarker or therapeutic target for the diagnosis or treatment of MS.